Community Empowerment Through Plastic Waste Recycling Activities into Ecobrick - Yuyun Andinar; Gilang Septiansyah; Ibrahim Bahri; Irwanda Hirwan; Hasni (Asian Journal of Community Services, 2023)
Waste is one of the complex problems faced by both developed and developing countries, especially plastic waste where plastic waste is difficult to decompose so it can damage the surrounding environment. The purpose of this empowerment is to educate the public on how to manage plastic waste with ecobricks. and how the impact of ecobrick on the surrounding community. The approach in this study uses qualitative methods with data collection techniques in the form of observation, interviews, and documentation. The research informants are the local people of Sanrobone Village. The research results show that there are six stages in empowering ecobricks (1) providing training on ecobricks, (2) collecting plastic waste, (3) sorting plastic waste, (4) doing ecobricks, (5) Weighing the ecobricks, (6) putting together the ecobricks.